A Case of Pelvic Abscess Caused By the Foley Catheter Remnant in the Bladder and Iatrogenic Urethra Rupture (Annals of Medical Research, 2021)
None
Keywords: Pelvic abscess, Pelvic fracture, Urethra rupture, Remnant Foley catheter.